Cabotegravir in the treatment and prevention of Human Immunodeficiency Virus-1. (3rd April 2018) - McPherson, Tristan D.; Sobieszczyk, Magdalena E.; Markowitz, Martin
ABSTRACT: Introduction: Human Immunodeficiency Virus (HIV) is a chronic infection that depletes the immune system of essential components causing those infected to be at risk for multiple life-threatening infections. Worldwide, millions live with this infection, the vast majority attributable to HIV-1. Transmission persists with hundreds of thousands of new infections reported yearly. Implementation of combination antiretroviral therapy (cART) has been effective in improving outcomes and decreasing transmission. Newer co-formulated agents have provided simpler medication regimens, fewer side effects, and, in some cases, a higher barrier to the emergence of medication resistance. Areas covered: Here, we review trials of cabotegravir (CAB) as treatment of HIV-1 infection and its potential use as pre-exposure prophylaxis (PrEP) in high risk individuals, including issues around oral lead in and potential resistance emergence. Expert opinion: CAB is efficacious when used in combination therapy orally or given intramuscularly every 4 to 8 weeks. Its availability in a long-acting injectable formulation (CAB-LA) makes it a valuable, novel drug to treat HIV-1 infection when combined with long-acting injectable rilpivirine (RPV-LA). Moreover, pre-clinical and early Phase 2a studies support its testing as monotherapy as PrEP. Studies are underway comparing the efficacy of every 8 week CAB-LA to tenofovir disoproxil fumarate/emtricitabine (TDF/FTC).